Determination of veterinary antibiotics in dairy manure slurry by LC-MS/MS. Issue 17 (8th November 2019) - Alam, Mahbub; Arikan, Osman Atilla; Yuksel, Ebubekir; Eyvaz, Murat; Gurbulak, Ercan; Gunaydin, Okan
Abstract: Veterinary antibiotics are used in the dairy animal for therapeutic purposes to better absorb nutrients and treat different diseases. However, developments of resistance against veterinary antibiotics which is generally disposed into the agricultural lands have been reported as a considerable concern. Therefore, this study was conducted to determine the veterinary antibiotics in dairy manure slurry obtained from three selected farms in various districts in the Marmara Region of Turkey. This study examined the quantification of monensin, lincomycin, amprolium and salinomycin in dairy manure samples by a liquid chromatography triple quadrupole mass spectrometry (LC-MS/MS). Atmospheric pressure ionization-tandem mass spectrometry was utilized on a benchtop triple quadrupole mass spectrometer operated in electrospray ionization (ESI) mode to analyze manure slurry samples. The procedures of the extraction and recovery studies were also stated. Graphical Abstract: